Application of the Fattaqun Method in Learning to Read and Write the Qur'an at MTs Nurul Qur'an The Benchmark of Kraksaan Probolinggo - Ipnu Ruslan Nuruzzaman; Amad Fauzi; Nur Fatima (CV. Rayyan Dwi Bharata, 2023)
Educational institutions are a place for children to learn to acquire knowledge and develop various abilities and skills. Therefore, teaching in schools is an effort that is conscious, purposeful, systematic and directed at changing behavior or attitudes. Changes in behavior can occur when the teaching process takes place in schools. Islam is a way of life. Therefore, the ability to write, read, understand, and at the same time live up to the contents of the readings of the Qur'an, especially in schools brought by religious institutions or general education, such as junior high schools (SMP) and Madrasah Aliyah schools (SMA) are very important in improving the morale of students. Therefore, as parents at school, teachers should pay attention to and be responsible for the development of students' understanding. Because a child's development is largely determined by the education and experience he goes through. Studying the Koran is actually not too difficult, as long as there is a will and effort to learn it, you will definitely be able to read and understand the Koran well, Allah has guaranteed its convenience. for people who study the Koran. The fattaqun method was developed by the BISMI (Intensive Islamic Guidance) institution based in Bandung. This method provides teaching so that those who cannot read the Koran can easily learn to read the Koran and can recognize the rules of tajwid science and the art of reading the Koran. This method is still not widespread in society, it is still used in institutions, education and Islamic boarding schools. It should be noted that lately there are many Qur'anic learning methods that have developed in society, and each of these methods has its own characteristics, in terms of objectives, selection of teaching materials, sequence of teaching material (Gradation), indicators of completeness, objectives, teaching techniques and evaluation techniques.